Comparative parallel execution of SWAT hydrological model on multicore and grid architectures. (24th September 2012) - Rodila, Denisa; Bacu, Victor; Gorgan, Dorian
The paper presents a comparative analysis made on the calibration of a large-scale model, executed both on grid and multicore architectures. The goal is to highlight the advantages brought by the grid infrastructure over the multicore architecture, especially for large-scale applications, which require large amounts of data and a large number of executions. The large-scale application used as a case study for this research work is the calibration of a large-scale SWAT hydrological model, covering the Danube River Basin.